NURS-09. INTRODUCTION OF SKIN CARE GUIDELINES FOR CHILDREN AND TEENS TAKING MOLECULARLY TARGETED AGENTS. Issue 2 (22nd June 2018) - Waters, Kaaren; Rangan, Kasey; Margol, Ashley; Robison, Nathan; Dhall, Girish; Evans, Anna
Abstract: Molecularly targeted therapies, such as MEK, BRAF, and EGFR inhibitors, are prescribed in pediatric neuro-oncology practice with increasing frequency. Although these targeted medications have demonstrated inhibition of tumor growth without traditional chemotherapy side effects, they are not without associated toxicities. Dermatologic findings are among the most commonly reported toxicities. Collaboration between providers, patients and families through prevention, early recognition, and promptly initiated treatment of associated skin toxicities can decrease strain and avoid interruption and/or early termination of these therapeutic agents resulting in overall increased treatment compliance. After an extensive review of the available published literature, a skin care teaching tool was created, in collaboration with nurse practitioners and physicians. The handout was implemented into practice to educate patients and families on preventative and early interventional measures to identify and treat skin toxicities related to treatment with targeted therapies. The fact sheet outlined the most common skin side effects including dry, itchy, scaly scalp and skin, cracked lips, dermatitis, acneiform rash, hair thinning, photosensitivity, ingrown and infected nails, and development of new moles. This introduction of skin care guidelines into a clinical neuro-oncology program represents a feasible and effective strategy for providing educational and supportive care to patients and families and preventing and treating skin toxicities associated with innovative targeted treatments. These guidelines can easily be initiated at other pediatric neuro-oncology practices, demonstrate adaptation in provider practice to newer oncology therapies, and exemplifies an evidence based collaborative team approach together with patients and families.